ANALISIS BIAYA PRODUKSI DENGAN PENDEKATAN THEORY OF CONSTRAINT UNTUK MENINGKATKAN LABA - dena evi suiani (JURNAL EKONOMI MANAJEMEN AKUNTANSI, 2012)
Approach of Theory of Constraint can increase profit by the way of minimiation of production cost. Data analysis in this research applies approach of theory of constraint done through phases, that is : identifies banding constraint, determines exploiting that is most efficient, manages stream produce and calculation throughput. Authenticity of data is done with credibility test, member check and discussion. Result of analysis with applying of TOC in identifying and manages production constraint, can be made consideration to increase throughput and profit improvement of company. Ever greater of throughput yielded hence ever greater also company profit.  Keywords : Theory of constraint, production cost, throughput, profit.